2017
DOI: 10.1017/s0007114517000769
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics to prevent necrotising enterocolitis and nosocomial infection in very low birth weight preterm infants

Abstract: The aim of the study was to determine whether routine probiotic supplementation (RPS) with Lactobacillus rhamnosus GG (LGG) or Lactobacillus acidophilus +Lactobacillus bifidum is associated with reduced risk of necrotising enterocolitis (NEC)≥Stage II in preterm neonates born at ≤32 weeks' gestation. We conducted a retrospective cohort study on the effect of probiotic supplementation in very low birth weight infants in our neonatal unit by comparing two periods: before and after supplementation. The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…Mechanisms of LGG actions against Salmonella are not fully understood, and bacterial interferences use different principles such as inhibition of adhesion and biofilm formation , production of lactic acid and others. Positive effects of LGG against enterocolitis in animal models or in infants have been observed. However, other authors did not confirm such beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of LGG actions against Salmonella are not fully understood, and bacterial interferences use different principles such as inhibition of adhesion and biofilm formation , production of lactic acid and others. Positive effects of LGG against enterocolitis in animal models or in infants have been observed. However, other authors did not confirm such beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants are highly susceptible to dysbiosis and infections that can culminate in early (EOS) or late onset of sepsis (LOS) . Probiotics are microbes that are commonly beneficial to their host and their application influences and supports the establishment of a balanced microbiota . Lactobacillus rhamnosus GG (LGG) belongs to a group of the most frequently used probiotic bacteria applied as a therapeutic agent .…”
Section: Introductionmentioning
confidence: 99%
“…A role for the mucins in the pathogenesis of NEC is indicated by the depletion of Goblet cells seen in the mucosa of neonates with NEC [ 432 , 433 , 434 ] and this is expected to represent a reduction of MUC2 in the secreted mucus gel. Evidence for abnormal microbiota causing NEC has been proposed [ 435 ] and probiotics ( Bifidobacillus and Lactobacillus strains) have been used in the treatment of the disease [ 436 , 437 , 438 ].…”
Section: Aberrant Mucin Glycosylation and Disease In The Gastroinmentioning
confidence: 99%
“…The disappointing results of the PiPs trial caused a major drawback for the use of probiotics in the management of the preterms. In 2017, Uberos conducted a retrospective cohort study evaluating clinical outcomes in VLBW infants, before and after the introduction of routinely probiotics supplementation with Lactobacillus rhamnosus GG (LGG) or Lactobacillus acidophilus (L. acidophilus) and Lactobacillus bifidum (L. bifidum) [ 25 ]. The authors observed a significant reduction in NEC ≥ Stage II (11.3 vs 4.8%), LOS (16 vs 10.5%) and mortality (19.4 vs 2.3%) in infants born before 32 weeks of gestational age (WGA), while in neonates aged ≤27 weeks the reduction was not statistically significant [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Uberos conducted a retrospective cohort study evaluating clinical outcomes in VLBW infants, before and after the introduction of routinely probiotics supplementation with Lactobacillus rhamnosus GG (LGG) or Lactobacillus acidophilus (L. acidophilus) and Lactobacillus bifidum (L. bifidum) [ 25 ]. The authors observed a significant reduction in NEC ≥ Stage II (11.3 vs 4.8%), LOS (16 vs 10.5%) and mortality (19.4 vs 2.3%) in infants born before 32 weeks of gestational age (WGA), while in neonates aged ≤27 weeks the reduction was not statistically significant [ 25 ]. In the same year, Aceti et al, on behalf of the Italian Society of Neonatology published another metanalysis of 25 trials on probiotics and LOS: probiotics’ supplementation resulted in a significantly lower incidence of LOS (RR 0.79) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%